An updated map of infauna associations for the southeastern North Sea with high spatial resolution inside Marine Protected Areas - Lars Gutow; Marko Rothe; Valentin Sauerbier; Tim Bildstein; Lasse Sander; Javier Lenzi; Chueh-Chen Tung; Jan Beermann; Kathrin Heinicke; Roland Pesch (Regional Studies in Marine Science, 2026)

Noisy waters affect feeding and metabolic enzyme activities of amphipod mesograzers - Sheng V. Wang; Anna Terschek; Nelly Tremblay; Maarten Boersma; Alexa Wrede; Jan Beermann (Marine Pollution Bulletin, 2026)

Offshore wind turbines constitute benthic secondary production hotspots on and around constructions - Jennifer Dannheim; Jan Beermann; Joop W.P. Coolen; Jan Vanaverbeke; Steven Degraer; Silvana N.R. Birchenough; Clement Garcia; Genevieve Lacroix; Dario Fiorentino; Han Lindeboom; Roland Krone; Hendrik Pehlke; et al. (Journal of Environmental Management, 2025)

Anthropogenic low-frequency sound effects on resting metabolism and energy pathways in two marine benthic crustaceans - Anna Terschek; Nelly Tremblay; Sheng V. Wang; Jan Beermann (Marine Biology, 2025)
Anthropogenic sound caused by ship traffic as well as the construction and operation of offshore windfarms have increased exponentially in the last decades. While its impact on marine life is relatively well studied for mammals and fish, the implications of anthropogenic sound on benthic invertebrates are poorly understood. Here, we tested for potential stress responses of common marine invertebrates using two widespread mesograzing crustaceans: the isopod Idotea balthica and the amphipod Gammarus locusta . All experimental animals were gathered from laboratory cultures in the facilities of the Alfred Wegener Institute in Bremerhaven, Germany, in spring 2023. Oxygen consumption rates and the activities of four key mitochondrial enzymes (cytochrome c oxidase, electron transport system complex I and III, citrate synthase and lactate dehydrogenase) were examined under the influence of added low-frequency sound (+ 25 dB SPL RMS re 1 µPa at 90 Hz, above background soundscape) to assess how basal energy demands and supplies were affected. The isopod I. balthica seemed to be robust against added sound exposure over 72 h as neither oxygen consumption rates nor enzyme activities were significantly altered. The amphipod G. locusta , however, displayed significantly lower oxygen consumption rates in response to both short-term (1–4 h; 39% reduction) and longer-term (68–72 h; 35% reduction) added sound exposure, although enzymatic activities were not significantly affected. This study underlines the need to address the potential impact of sound on the energy available for the growth and reproduction of small invertebrates. Overlooked vulnerabilities to noise pollution in key taxa could have far reaching implications for marine food webs, nutrient cycles and ecosystem functioning.

Fit for purpose? Evaluating benthic invertebrate DNA metabarcoding for ecological status class assessment in streams under the Water Framework Directive - Till-Hendrik Macher; Arne J. Beermann; Jens Arle; Julia Foerster; Matthias Greyer; Demetrio Mora; Jan Koschorreck; Peter Rolauffs; Anne Rother; Susanne Schüler; Jonas Zimmermann; Daniel Hering; et al. (Water Research, 2025)

Musseling through: Mytilus byssal thread production is unaffected by continuous noise - Sheng V. Wang; Julius A. Ellrich; Jan Beermann; Bernadette Pogoda; Maarten Boersma (Marine Environmental Research, 2024)

DNA metabarcoding reveals a diverse, omnivorous diet of Arctic amphipods during the polar night, with jellyfish and fish as major prey - Annkathrin Dischereit; Jan Beermann; Benoit Lebreton; Owen S. Wangensteen; Stefan Neuhaus; Charlotte Havermans (Frontiers in Marine Science, 2024)
Introduction Currently, Arctic marine ecosystems are witnessing the most rapid physical changes worldwide, leading to shifts in pelagic and benthic communities and food web structure, concomitant with the introduction of boreal species. Gelatinous zooplankton or jellyfish represent one particular group of which several boreal species are prone to undergo significant poleward range expansions and population increases in the Arctic in the course of the ongoing changes. Historically, jellyfish were considered a trophic dead-end, but an increasing number of studies using modern tools have highlighted their role as major prey items in marine food webs. In this study, we aimed to verify the role of jellyfish and other metazoans as food sources in the Arctic polar night food web, when pelagic resources are limited. Methods We identified the diet of different bentho-pelagic amphipod species in the Atlantifying Kongsfjorden (West Svalbard) during the polar night. We regularly sampled lysianassoid and gammarid amphipods using baited traps and hand nets over a period of one month during the polar night and identified their diet spectrum by applying DNA metabarcoding (COI) to their stomach contents. Results We demonstrate that all investigated species are omnivorous. Fish species including polar cod and snailfish, likely in the shape of carrion, played an important role in the diet of the scavengers Orchomenella minuta and Anonyx sarsi . Predation and potential scavenging on jellyfish contributed to the diet of all four investigated species, particularly for the species Gammarus setosus and G. oceanicus , as evidenced by high read abundances and high frequencies of occurrence. Besides jellyfish, crustaceans and macroalgae were important components of the diet of the two Gammarus species. Discussion The diverse jellyfish community present in Kongsfjorden in the polar night is clearly being utilized as a food source, either through pelagic feeding or feeding on jelly-falls, albeit to a different extent in the local amphipod community. These findings provide novel insights into the Arctic food web during the polar night and represent the first evidence of feeding on natural (non-experimental) jelly-falls.

Characterization and differentiation of sublittoral sandbanks in the southeastern North Sea - Jan Beermann; Lars Gutow; Steffen Wührdemann; Rebecca Konijnenberg; Kathrin Heinicke; Tim Bildstein; Sandra Jaklin; Manuela Gusky; Michael L. Zettler; Jennifer Dannheim; Roland Pesch (Biodiversity and Conservation, 2023)
Marine sublittoral sandbanks are essential offshore feeding grounds for larger crustaceans, fish and seabirds. In the southern North Sea, sandbanks are characterized by considerable natural sediment dynamics and are subject to chronic bottom trawling. However, except for the Dogger Bank, sandbanks in the southeastern North Sea have been only poorly investigated until now. We used an extensive, multi-annual dataset covering ongoing national monitoring programmes, environmental impact assessments, and basic research studies to analyse benthic communities on sublittoral sandbanks, evaluating their ecological value against the backdrop of similar seafloor habitats in this region. The analysis revealed complex spatial structuring of sandy seafloor habitats of the southeastern North Sea. Different infauna clusters were identified and could be specified by their composition of characteristic species. The sandbanks shared common structural features in their infauna community composition although they were not necessarily characterized by particularly high biodiversity compared to other sandy habitats. A close association of one of the main bioturbators in the southern North Sea, the sea urchin Echinocardium cordatum , with sandbanks was detected, which may promote the sediment-bound biogeochemical activity in this particular seafloor habitat. This would corroborate the status of sandbanks as sites of high ecological value calling for consideration in marine conservation.

Umwelt-DNA-basiertes Monitoring an der Fischtreppe Dessau-Roßlau: Ein Vergleich mit fischereilichen Methoden - Till-Hendrik Macher; Robin Schütz; Arne J. Beermann; Florian Leese; Falko Wagner; Jens Arle; Jan Koschorreck (WASSERWIRTSCHAFT, 2023)

The role of systematics for understanding ecosystem functions: Proceedings of the Zoologica Scripta Symposium, Oslo, Norway, 25 August 2022 - Lutz Bachmann; Jan Beermann; Thomas Brey; Hugo J. de Boer; Jennifer Dannheim; Bente Edvardsen; Per G. P. Ericson; Kevin C. Holston; Veronika A. Johansson; Paul Kloss; Rebecca Konijnenberg; Karen J. Osborn; et al. (Zoologica Scripta, 2023)
On 25 August 2022, the Zoologica Scripta ‐ An International Journal of Systematic Zoology and the Norwegian Academy of Sciences and Letters arranged a symposium entitled ‘The role of systematics for understanding ecosystem functions’ in the Academy's premises in Oslo, Norway. The symposium aimed at offering a forum for exploring and discussing trends and future developments in the field of systematics. Eleven international experts contributed expertise on various issues related to global challenges, such as biodiversity assessments, databases, cutting‐edge analysis tools, and the consequences of the taxonomic impediment. Here, we compiled a multi‐author proceedings paper of the symposium contributions that are arranged in chapters and presents the content and the key conclusions of the majority of the presentations.

The interplay of temperature and algal enrichment intensifies bioturbation of the intertidal amphipod Corophium volutator - Eilish M. Farrell; Jan Beermann; Andreas Neumann; Alexa Wrede (Journal of Experimental Marine Biology and Ecology, 2023)

The Discovery and Preliminary Geological and Faunal Descriptions of Three New Steinahóll Vent Sites, Reykjanes Ridge, Iceland - James Taylor; Colin Devey; Morgane Le Saout; Sven Petersen; Tom Kwasnitschka; Inmaculada Frutos; Katrin Linse; Anne-Nina Lörz; Dominik Pałgan; Anne H. Tandberg; Jörundur Svavarsson; Daniel Thorhallsson; et al. (Frontiers in Marine Science, 2021)
During RV MS Merian expedition MSM75, an international, multidisciplinary team explored the Reykjanes Ridge from June to August 2018. The first area of study, Steinahóll (150–350 m depth), was chosen based on previous seismic data indicating hydrothermal activity. The sampling strategy included ship- and AUV-mounted multibeam surveys, Remotely Operated Vehicle (ROV), Epibenthic Sledge (EBS), and van Veen grab (vV) deployments. Upon returning to Steinahóll during the final days of MSM75, hydrothermal vent sites were discovered using the ROV Phoca (Kiel, GEOMAR). Here we describe and name three new, distinct hydrothermal vent site vulnerable marine ecosystems (VMEs); Hafgufa, Stökkull, Lyngbakr. The hydrothermal vent sites consisted of multiple anhydrite chimneys with large quantities of bacterial mats visible. The largest of the three sites (Hafgufa) was mapped, and reconstructed in 3D. In total 23,310 individual biological specimens were sampled comprising 41 higher taxa. Unique fauna located in the hydrothermally venting areas included two putative new species of harpacticoid copepod ( Tisbe sp. nov. and Amphiascus sp. nov.), as well as the sponge Lycopodina cupressiformis (Carter, 1874). Capitellidae Grube, 1862 and Dorvilleidae Chamberlin, 1919 families dominated hydrothermally influenced samples for polychaetes. Around the hydrothermally influenced sites we observed a notable lack of megafauna, with only a few species being present. While we observed hydrothermal associations, the overall species composition is very similar to that seen at other shallow water vent sites in the north of Iceland, such as the Mohns Ridge vent fields, particularly with peracarid crustaceans. We therefore conclude the community overall reflects the usual “background” fauna of Iceland rather than consisting of “vent endemic” communities as is observed in deeper vent systems, with a few opportunistic species capable of utilizing this specialist environment.

Marine stepping‐stones: Connectivity of Mytilus edulis populations between offshore energy installations - Joop W. P. Coolen; Arjen R. Boon; Richard Crooijmans; Hilde van Pelt; Frank Kleissen; Daan Gerla; Jan Beermann; Silvana N. R. Birchenough; Leontine E. Becking; Pieternella C. Luttikhuizen (Molecular Ecology, 2020)
Recent papers have suggested that epifaunal organisms use artificial structures as stepping‐stones to spread to areas that are too distant to reach in a single generation. With thousands of artificial structures present in the North Sea, we test the hypothesis that these structures are connected by water currents and act as an interconnected reef. Population genetic structure of the blue mussel, Mytilus edulis , was expected to follow a pattern predicted by a particle tracking model (PTM). Correlation between population genetic differentiation, based on microsatellite markers, and particle exchange was tested. Specimens of M. edulis were found at each location, although the PTM indicated that locations >85 km offshore were isolated from coastal subpopulations. The fixation coefficient F ST correlated with the number of arrivals in the PTM. However, the number of effective migrants per generation as inferred from coalescent simulations did not show a strong correlation with the arriving particles. Isolation by distance analysis showed no increase in isolation with increasing distance and we did not find clear structure among the populations. The marine stepping‐stone effect is obviously important for the distribution of M. edulis in the North Sea and it may influence ecologically comparable species in a similar way. In the absence of artificial shallow hard substrates, M. edulis would be unlikely to survive in offshore North Sea waters.

Obituary: Siv Aina Jensen Leendertz (Born Siv Aina Jensen: 1973–2018) - Chantal Akoua-Koffi; Sandra Beermann; Sébastien Calvignac-Spencer; Emmanuel Couacy-Hymann; Helene De Nys; Bernhard Ehlers; Thomas Gillespie; Jeffrey Gilbert; Jan F. Gogarten; Sandra J. Laney; Felix Lankester; Fabian H. Leendertz; et al. (International Journal of Primatology, 2018)

Combined effects of predator cues and competition define habitat choice and food consumption of amphipod mesograzers - Jan Beermann; Karin Boos; Lars Gutow; Maarten Boersma; Ana Carolina Peralta (Oecologia, 2018)

Erratum to: The influence of intrinsic and extrinsic factors on developmental parameters and their relationships in the marine isopod Idotea linearis (Crustacea) - Heinz-Dieter Franke; Jan Beermann (Hydrobiologia, 2014)

The influence of intrinsic and extrinsic factors on developmental parameters and their relationships in the marine isopod Idotea linearis (Crustacea) - Heinz-Dieter Franke; Jan Beermann (Hydrobiologia, 2014)

Differences in resource utilization and behaviour between coexisting Jassa species (Crustacea, Amphipoda) - Jan Beermann; Heinz-Dieter Franke (Marine Biology, 2012)